5' Untranslated Region Elements Show High Abundance and Great Variability in Homologous ABCA Subfamily Genes - Dvorak, Pavel; Hlavac, Viktor; Soucek, Pavel (International journal of molecular sciences, 2020)
The 12 members of the ABCA subfamily in humans are known for their ability to transport cholesterol and its derivatives, vitamins, and xenobiotics across biomembranes. Several ABCA genes are causatively linked to inborn diseases, and the role in cancer progression and metastasis is studied intensively. The regulation of translation initiation is implicated as the major mechanism in the processes of post-transcriptional modifications determining final protein levels. In the current bioinformatics study, we mapped the features of the 5' untranslated regions (5'UTR) known to have the potential to regulate translation, such as the length of 5'UTRs, upstream ATG codons, upstream open-reading frames, introns, RNA G-quadruplex-forming sequences, stem loops, and Kozak consensus motifs, in the DNA sequences of all members of the subfamily. Subsequently, the conservation of the features, correlations among them, ribosome profiling data as well as protein levels in normal human tissues were examined. The 5'UTRs of ABCA genes contain above-average numbers of upstream ATGs, open-reading frames and introns, as well as conserved ones, and these elements probably play important biological roles in this subfamily, unlike RG4s. Although we found significant correlations among the features, we did not find any correlation between the numbers of 5'UTR features and protein tissue distribution and expression scores. We showed the existence of single nucleotide variants in relation to the 5'UTR features experimentally in a cohort of 105 breast cancer patients. 5'UTR features presumably prepare a complex playground, in which the other elements such as RNA binding proteins and non-coding RNAs play the major role in the fine-tuning of protein expression.
Keywords: Introns; 5' Untranslated Regions; výpočetní biologie; Protein Biosynthesis; ABCA subfamily; lidé; Multigene Family; bioinformatics; introny; Humans; Polymorphism, Single Nucleotide; Ribosomes; 5′ untranslated region; Biological Transport; ABC transportér, podrodina A; jednonukleotidový polymorfismus; otevřené čtecí rámce; ribozomy; cis-acting elements; xenobiotika; Computational Biology; Cholesterol; cholesterol; Open Reading Frames; proteosyntéza; Xenobiotics; multigenová rodina; biologický transport; 5' nepřekládaná oblast; ATP Binding Cassette Transporter, Subfamily A; ABC transporters